River water temperature demonstrates resistance to long‐term air temperature change. Issue 11 (1st November 2022) - Worrall, Fred; Howden, Nicholas J. K.; Burt, Tim P.; Hannah, David M.
Abstract: Ecosystem health and water quality of rivers are dependent on their temperature. With ongoing human‐induced climate change causing increases in air temperature across the globe, it is anticipated the stream temperatures will rise too—in turn increasing the rates of biogeochemical stream processes and potentially threatening the viability and health of aquatic organisms. To understand the relationship between climate change and stream temperature response, the longer the records that can be analysed, the more the robust the analysis for detecting change. In this study, we analyse records from 263 catchments from across the United Kingdom for 45 years from 1974 to 2019 to assess the link between air temperature and stream temperature change. To give the most precise analysis of these long records, Bayesian hierarchical modelling was used and showed that: (i) The Bayesian hierarchical approach was 59% more precise, that is, reduced uncertainty on long‐term trends, than using simple linear regression. (ii) The increase in annual average air temperature over 45 years across the United Kingdom showed no significant differences between 22 weather stations and gave a 45‐year change of 1.35 ± 0.9°C. (iii) Trends in annual mean stream temperature change varied from −2.3 °C to 2.0 °C over 45 years, with the mean over 263 sites being 0.5 °C over 45 years. (iv) 1% of rivers showed a stream temperature trend significantly greater than the air temperature trend but 3% of sites showed a stream temperature trend significantly lower than zero. (v) 74% of all river sites showed no significant monotonic trend, either positive or negative, in water temperature even after 45 years. The observed declines in stream temperature could be ascribed to the closures of thermoelectric power stations but it is unclear why the stream temperature at some sites has risen faster than air temperature. The study shows that mean river temperature was well buffered against changes in air temperature—a 1°C rise in air temperature giving 0.37°C in mean stream temperature. Abstract : River water temperature demonstrates resistance to long‐term air temperature change.